Effect of parsley (Petroselinum crispum) on the skin of STZ induced diabetic rats - (:unkn) unknown (WILEY, 1999)
Parsley (Petroselinum crispum) is one of the medicinal herbs used by diabetics in Turkey and it has been reported to reduce blood glucose. The purpose of this study therefore was to investigate the effect of feeding parsley on diabetes induced impairments in rat skins. Uncontrolled induced diabetes caused significant increases in nonenzymatic glycosylation of skin proteins, lipid peroxidation and blood glucose. Administration of parsley extract did not inhibit these effects except for the increase in blood glucose. SDS-polyacrylamide gel electrophoresis revealed no significant differences in any protein bands between any of the groups. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: skin; diabetes; parsley; nonenzymatic glycosylation; lipid peroxidation; protein electrophoresis; NONENZYMATIC GLYCATION; PROTEINS; MELLITUS; PRODUCTS; MICE